Methods for increasing wear resistance of working bodies of single-bucket excavators - Ruzibaev Alisher; Toshov Buri; Muminov Rashid; Tukhtaev Bobirjon; Kadirov Xalim; Namozova Zuxra (E3S Web of Conferences)
This article examines the geometry, shape, design, and material selection of excavator bucket teeth. It highlights the importance of optimizing tooth shape to match the material being processed, ensuring favorable load dynamics, sufficient wear resistance, ease of replacement for worn teeth, and minimal energy consumption during soil excavation. The study emphasizes that wear on moving parts can lead to a reduction in excavator reliability and durability, with failures attributed to wear accounting for 80–90% of operational issues. Excavator components are subjected to various types of wear, including abrasive, hydro-abrasive, cavitation, and erosive wear. The research demonstrates that the extent of wear is influenced by a wide range of operational factors and follows statistical and mathematical laws. Express ratios are introduced to facilitate the self-sharpening effect, which helps stabilize the thickness of the cutting edge during wear. Additionally, formulas are proposed for calculating conditions that contribute to abrasive wear in excavator parts.